Metafilozofia negatywistycznej metafizyki unitarnej Leszka Nowaka - Kiedrowski, Krzysztof (Człowiek i Społeczeństwo, 2022)
The theme of this paper is Leszek Nowak’s reconstruction and systematization of metaphilosophy of the negativistic unitarian metaphysics described in Being and Thought in four volumes, published in the years 1998, 2004, 2007, 2019. The goal of the article is to contribute to the discussion on the status of metaphilosophy. Metaphilosophy is understood here as a separate dimension of every philosophical conception determining, on the one hand, how we understand the realm of objects (what we postulate), on the other hand, how we choose methods for the construction of theories and ways to legitimize them. The author tries to show that Nowak’s metaphilosophy assumed in negativistic unitarian metaphysics meets exactly this definition of metaphilosophy.